PENERAPAN METODE DMAIC DALAM PENGENDALIAN KUALITAS PRODUK CACAT PADA PABRIK PIE SUSU PUTRI THE APPLICATION OF THE DMAIC METHOD IN QUALITY CONTROL OF DEFECTIVE PRODUCTS AT PIE SUSU PUTRI FACTORY - Dewa Putu Waruna Agung; Anak Agung Istri Agung Sri Komaladewi; I Gusti Agung Kade Suriadi (PT. Hasba Edukasi Mandiri, 2026)
Product quality is an important factor in maintaining competitiveness and customer satisfaction. Pie Susu Putri Factory, as a local food producer, still faces problems related to the high rate of defective products, including burnt, broken, and chipped pies. This study aims to improve product quality at Pie Susu Putri Factory by applying the Six Sigma method through the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The main problem identified was the high number of defective products such as burnt, broken, and chipped pies. The Define stage identified four Critical to Quality (CTQ) characteristics. In the Measure stage, a DPMO value of 14,901 and a sigma level of 3.67 were obtained, indicating that the process did not yet meet the Six Sigma standard. Analysis using a fishbone diagram and scatter plot showed that the main causes originated from oven temperature, pie release technique, and dough thickness. Improvements were carried out through monitoring, operator training, and equipment maintenance.